Chemical profiles, pharmacological properties, and in silico studies provide new insights on Cycas pectinata. Issue 6 (June 2020) - Tareq, Abu Montakim; Farhad, Saifuddin; Neshar Uddin, A.B.M.; Hoque, Muminul; Nasrin, Mst. Samima; Uddin, Mir Md. Rokib; Hasan, Mohiminul; Sultana, Arafat; Munira, Mst. Shirajum; Lyzu, Chadni; Moazzem Hossen, S.M.; Ali Reza, A.S.M.; et al.
Abstract: The current study aimed to qualitatively and quantitatively determine the phytochemical components of Cycas pectinata methanol extract (MECP), along with its antioxidant, anti-inflammatory, thrombolytic, locomotor, anxiolytic, analgesic, and antidiarrheal activities. The in vitro antioxidant activity was evaluated by DPPH scavenging assay and the total phenol and total flavonoid contents, while the anti-inflammatory activity was evaluated by a protein denaturation assay. The in vivo locomotor effects were examined using the open field test and hole-cross test. The anxiolytic effect was examined using the elevated plus maze (EPM) test, hole-board test (HBT), and light–dark test (LDT), while the analgesic activity was investigated using the acetic acid-induced writhing test. The antidiarrheal effect was evaluated by castor oil-induced diarrhea and gastrointestinal motility. Ten bioactive compounds were selected on the basis of their biological activities and further investigated using in silico molecular docking simulation to correlate with the identified pharmacological properties. Additionally, the ADME properties of the compounds were evaluated according to their drug-likeness profile. MECP had a maximum total phenol content of 209.85 ± 3.40 gallic acid equivalents/g extract and a total flavonoid content of 105.17 ± 3.45 quercetin equivalents/g extract, with an IC50 value of 631.44 μg/mL. MECP (62.5–500 μg/mL) elicited 20.96–38.12% decreased protein denaturation compared to diclofenac sodium (65.40–83.50%), while a 35.72% (P < 0.001) clot lysis activity was observed for the 10 mg/mL concentration. MECP induced a dose-dependent reduction in locomotor activity, with a significant anxiolytic effect. In the analgesic test, MECP (200, 400 mg/kg) showed a 45.12% and 58.82% inhibition in analgesia, and the 400 mg/kg dose elicited a 27.5% inhibition in intestinal motility. These findings suggest that MECP might be effective in treating antioxidant, anti-inflammatory, and neuropharmacological defects, but this requires further study. Abstract : Cycas pectinata ; Antioxidant; Anxiolytic; Analgesic; Anti-inflammatory; Plant biology; Bioinformatics; Pharmaceutical science; Alternative medicine; Evidence-based medicine